Alberto Patishtán Gómez: radiography of a late pardon - Muñoz Vargas, Osvaldo Antonio (2016)
The autor illustrates the Patishtán Gómez’ case (Chiapas, Mexico, 2000), in which the facts that took place at Las Lagunas de Las Limas, Simojovel are shown chronologically. The importance to point out this case is to overestimate the violations of the human rights process more than the depth of the criminal law. In this specific case, the author pretends to analyze it from a strict political viewpoint, leaving any anthropological research behind because by having reread it, it can be easily inferred that there was ethnic discrimination.